2017
DOI: 10.1111/ijfs.13362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of culture substrates on taste component content and taste quality of Lentinula edodes

Abstract: Summary In this research, the effects of culture substrates on taste component content of Lentinula edodes were studied, and the resulting taste quality of L. edodes was evaluated. The results revealed that single‐carbon and single‐nitrogen sources were beneficial to production of soluble sugars and polyols, organic acids and sweet amino acids, whereas a single‐carbon source was beneficial to essential amino acid production, and a mixed‐carbon source was beneficial to umami 5′‐nucleotides and high mushroom pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…In our previous studies, we found that succinic acid, citric acid, and malic acid were the main organic acids in Lentinula edodes fruit bodies (Chen et al., ), fumaric acid was the major organic acid in Pleurotus cystidiosus fruit bodies, and citric acid was the major organic acid in Agaricus blazei fruit bodies (Li et al., ). For several different mushroom strains, culture substrates, drying methods, and stage of harvest all had large effects on the production of taste components (Chen et al., ; Li et al., , , , ), were the reason for and the differences in organic acid type and content. Lactic acid, arising from the microbial fermentation of carbohydrates, could develop food probiotic products with improved nutritional quality (Divya, Varsha, Nampoothiri, Ismail, & Pandey, ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we found that succinic acid, citric acid, and malic acid were the main organic acids in Lentinula edodes fruit bodies (Chen et al., ), fumaric acid was the major organic acid in Pleurotus cystidiosus fruit bodies, and citric acid was the major organic acid in Agaricus blazei fruit bodies (Li et al., ). For several different mushroom strains, culture substrates, drying methods, and stage of harvest all had large effects on the production of taste components (Chen et al., ; Li et al., , , , ), were the reason for and the differences in organic acid type and content. Lactic acid, arising from the microbial fermentation of carbohydrates, could develop food probiotic products with improved nutritional quality (Divya, Varsha, Nampoothiri, Ismail, & Pandey, ).…”
Section: Resultsmentioning
confidence: 99%
“…Gürgen and Yildiz [80] showed that pretreatment with citric acid in P. citrinopileatus helps to protect their yellow color when fruit bodies were dried. As for malic acid, it is often added to foods as an acidic additive to improve the organoleptic properties of foods [69]. The results showed in our work require extensive research in order to indicate what mechanism is associated with an increase in the contents of acids in fruit bodies.…”
Section: Discussionmentioning
confidence: 79%
“…It should be remembered that the type of substrate and added waste determine not only the chemical composition of fruit bodies but also affect their functional and sensory properties, because these substrates may contain biologically active compounds. Studied LMWOAs are closely related to the synthesis of amino acids, phenols and esters, with the metabolism of aroma components [69]. In mushrooms acids additionally affect taste and aroma attributes [70], while they are also used as a factor extending their shelf life and suitability for consumption thanks to their antibacterial and antioxidant properties [71].…”
Section: Discussionmentioning
confidence: 99%
“…However, under SCG supplementation the production of acids was significantly inhibited. Such information is very useful because LMWOAs are important constituents of mushroom taste and have a close relation to amino acids, phenols, and ester synthesis, and also play a part in the metabolic processes of aroma components (Li et al, 2017) and special flavor (Yang, Gu, Liu, Zhou, & Zhang, 2013). In this study, quinic acid was found to be the major acid in P. eryngii fruiting bodies harvested from the TPEW variants.…”
Section: Profile and Content Of Low-molecularweight Organic Acidsmentioning
confidence: 99%
“…An increased level of succinic acid is characterized as a flavor component. Succinic acid and sodium succinate have an umami flavor and could be used as seasonings (Li et al, 2017) as well as malic acid, which is also often added to food as a sour additive to improve its organoleptic characteristics (Li et al, 2014;Zheng, Zhang, & Qi, 2012).…”
Section: Profile and Content Of Low-molecularweight Organic Acidsmentioning
confidence: 99%